Legal Analysis of Inmate Development to Optimize the Correctional System in Cirebon Prison - Kowasmar Putra, Suyadi; Hamamah, Fatin; Walim, Walim (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: This article examines the legal and practical framework of inmate development within Indonesia’s correctional system following the enactment of Law Number 22 of 2022 on Corrections. It highlights ongoing challenges in ensuring that correctional institutions effectively fulfill their rehabilitative mandate, with Cirebon Class IIA Correctional Facility serving as the primary locus of analysis.Purposes of the Research: The purpose of this study is to analyze the legal regulation of inmate development under Law Number 22 of 2022, evaluate its implementation in Cirebon Class IIA Correctional Facility, and identify inhibiting factors as well as the institutional efforts undertaken to optimize inmate development in accordance with national correctional standards.Methods of the Research: This research employs a descriptive qualitative design combining normative and empirical juridical approaches. Secondary legal materials from primary and secondary sources underpin the analysis. Data interpretation uses a deductive reasoning model through syllogistic analysis to assess the alignment of legal norms with on-ground practices in the implementation of inmate development programs.Findings of the Research: This study confirms that the Cirebon Class IIA Correctional Institution has made great efforts to fulfill the rights of inmates in accordance with the mandate of the Law on Corrections, which is manifested in the implementation of spiritual, social, health, and vocational development programs. These institutional efforts include the provision of routine religious guidance, psychological and social counseling, health seminars, and vocational skills training such as carpentry, agriculture, and handicrafts. However, the optimal implementation of these programs is severely hampered by significant structural challenges, namely severe overcapacity of inmates, limited number of correctional personnel and professional experts (psychologists, social workers, vocational instructors), and inadequate facilities and infrastructure to accommodate and support development activities effectively. The study highlights the gap between the ideal legal framework (das sollen) and the operational reality on the ground (das sein), while also demonstrating collaborative initiatives with external parties and proposals to increase resource allocation as mitigation measures.